AN EXPERIMENTAL STUDY ON EFFECT OF MAGNETIC WATER ON COMPRESSIVE STRENGTH CONCRETE - MR. SAGAR C. ASHTEKAR; PROF. JAWALKAR G. C. (International Journal of Innovations in Engineering Research and Technology, 2021)
In this research study, the effect of magnetized water on compressivestrength of concrete was studied.Data were collected from previous studies and researches. The magnetized water was prepared using the magnetic treatment system; it is device which called as magnetic water conditioner. Thistest was carried on threedifferent grades of concrete which is M25, M30, and M35.Four concrete mixes were prepared, one without magnetized water and three with. Compressivestrength tests were carried out on all four mixes and it was found out that concrete produced by the magnetic technology is easy to operate without affecting the compressive strength of concrete. It was also found that magnetized water increases the compressive strengthof concrete up to14%